Applications of electrochemistry in medicine Mordechay Schlesinger, editor. - Schlesinger, Mordechay (Modern aspects of electrochemistry, 2013)
This book describes the use of electrochemistry in medicine. Topics include electrochemistry in the design and development of medical technologies and devices, medical devices at the interface of biology and electrochemistry, and sensing by screen printed electrodes for medical diagnosis.